Restrukturisasi Kognitif Islam: Sebuah Perspektif Islamic Cognitive Behavior Therapy (I-CBT) - Rahma Fithri; Khairunnas Rajab (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Cognitive restructuring is a core technique in Cognitive Behavior Therapy (CBT) aimed at identifying and transforming negative or dysfunctional thought patterns into more adaptive and realistic ones. In Muslim communities, conventional CBT faces challenges when applied without considering spiritual dimensions and Islamic values. Islamic Cognitive Behavior Therapy (I-CBT) emerges as an integrative response that combines CBT principles with Islamic teachings, particularly the Qur'an, Hadith, and Islamic psychological concepts such as qalb, aql, and nafs. This study aims to comprehensively examine the concept of Islamic cognitive restructuring through the I-CBT lens, encompassing theological foundations, therapeutic processes, and its relevance in contemporary Islamic counseling practice. Using a literature review approach, this study finds that Islamic cognitive restructuring does not merely modify negative thoughts but also integrates dimensions of tawhid, tawakkul, sabr, and shukr as revelation-based cognitive change agents. Practical implications of I-CBT demonstrate significant effectiveness in improving learning motivation, self-esteem, self-acceptance, resilience, and reducing anxiety and addiction among Muslim populations. These findings affirm that integrating Islamic values into cognitive restructuring not only strengthens the cultural validity of therapy but also adds a transcendental dimension that provides meaning and hope for Muslim clients.